Wednesday

January 28, 2015

January 28, 2015

Posted by **Anonymous** on Monday, February 20, 2012 at 10:22pm.

[cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx]

= [cosx-(sin90cosx-cos90sinx)sinx]/[cosx-(cos180cosx+sinx180sinx)tanx]

= [cosx-((1)cosx-(0)sinx)sinx]/[cosx-((-1)cosx+(0)sinx)tanx]

= [cosx-cosxsinx]/[cosx+cosxtanx]

= [cosx(1-sinx]/[cosx(1+tanx]

= (1-sinx)/(1+tanx)

Is this correct???

- Trigonometry Check -
**Steve**, Tuesday, February 21, 2012 at 11:31amlooks good to me

**Answer this Question**

**Related Questions**

Trigonometry - Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/...

Math 12 - Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/sinx+...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...

maths - trigonometry - I've asked about this same question before, and someone ...

Mathematics - Trigonometric Identities - Prove: (tanx)(sinx) / (tanx) + (sinx...

Trig........ - I need to prove that the following is true. Thanks (cosx / 1-sinx...

Mathematics - Trigonometric Identities - Prove: sinx + tanx = tanx (1 + cosx) ...

Math - Im really struggling with these proving identities problems can somebody ...

Precalculus/Trig - I can't seem to prove these trig identities and would really ...